DEPRESSION AND ANXIETY IN PATIENT WITH ACUTE CORONARY SYNDROME - Kadek Dwi Krisnayanti (E-Jurnal Medika Udayana, 2013)
Depression and anxiety are two conditions that common happened in patient with acute coronary syndrome which can cause negative cardiovascular outcomes. Although the prevalencies of these two conditions are slightly high, most of them had not been treated well. The mechanisms that underly the association between depression and anxiety with the negative cardiovascular outcome are possibly correlates with their effect on inflammatory process, cathecolamine release, heart rate variability, endothelial function and also their effect on health promoting behavior. Fortunately, the standard therapies that available for these conditions are safe, effective, and can be tolerated well in most patients.